Intracellular glutathione in the protection from anoxic injury in renal proximal tubules. - Mandel, L J (1990)
Previous results (Weinberg, J. M., J. A. David, M. Abarzua, and T. Rajan. 1987. J. Clin. Invest. 80:1446-1454) have shown that GSH and glycine (GLY) are cytoprotective during anoxia when added extracellularly. The present studies investigate the role that intracellular GSH plays in this cytoprotection. Proximal renal tubules in suspension prepared with either high (11 +/- 1 nmol/mg protein) or low (6 +/- 1 nmol/mg protein) GSH contents were subjected to 40 min of anoxia and 40 min of reoxygenation. Low GSH tubules were protected from plasma membrane damage during anoxia by exogenous addition of 1 mM GSH or GLY, reducing lactate dehydrogenase (LDH) release from 42 +/- 7 to 14 +/- 1 and 10 +/- 1%, respectively. High GSH tubules were equally protected from anoxic damage without exogenous additions. Since the high GSH content approximates the in vivo values, it may be concluded that GSH may be cytoprotective during anoxia in vivo. However, it is not the intracellular GSH itself that is cytoprotective; rather, this protection resides in the ability to produce GLY, which appears to be the cytoprotective agent. Alanine was also shown to have similar cytoprotective properties, although higher concentrations were required. Sulfhydryl reducing agents such as cysteine and dithiothreitol offered less, but significant protection from anoxic damage. Protection by GSH, GLY, or alanine was not associated with higher ATP levels during anoxia. Tubules that were protected from membrane damage during anoxia recovered oxygen consumption and K and ATP contents significantly better during reoxygenation than unprotected tubules.